Stem cells and tissue regeneration - Nowicka, Grażyna (Studia Ecologiae et Bioethicae, 2005)
Stem cells there are undifferentiated, primitive cells with ability to differentiate into specific kinds of cells. Stem cell research has a history of more than 20 years and has made an outstanding contribution to our understanding of haematopoiesis and embryology. Stem cells hold the promise of allowing researchers to grow specialized cells or tissue, which could be used for treatment of injured tissues. Development of this area depends on the results of ethical debate over stem cel research, which is controversial, because the most powerful human stem cells there are embryonic stem cells. Adult bone marrow has been found as an important source of adult stem cells. Adult stem cells have been used in animal and human studies for tissue regeneration. The utility of stem cell transplantation for the treatment of acute myocardial infarction to repair of injured myocardium has been shown.